KOMERSIALISASI HAK CIPTA YANG TIDAK BERLISENSI PADA PLATFROM OVER-THE-TOP - Asrofi, Muchtar Hasan (Fakultas Hukum Universitas Islam Indonesia, 2024)
Vision+ (PT MNC OTT) becomes one of the live-streaming-subscription platform or the Over-The-Top subscription platform that has been receiving agreement/ license from FIFA through AFC to broadcast contents of Round 3 of 2026 World Cup Qualification Asia Zone. Vision+ is also a subscription broadcasting enterprise, so everyone who wants to use the platform and watch the contents has to create personal account and pay subscription fee. Sometimes, the platform is used by its user to make a profit (commercialization). For example, the café owner uses the personal account to broadcast the content of sport event to public. That case is our concern or object in this research. The aim of this research is to know the legal perspective of commercialization of the use of the live-streaming-platform personal account. This researchis normative legal research using statute and conceptual approaches. The result of this research is the café owner breaks the provisions of Law Number 28 of 2014 concerning Copyrights, Article 9 Paragraph (1) letter g, because the café owner broadcasts or announces the audio-visual content (economic right) without permission or license from copyrights holder which is Vision+.